2011
DOI: 10.2174/138161211796390994
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Inhibitors of Apoptosis in Cardiovascular Diseases

Abstract: Apoptosis or progress of programmed cell death is a tightly regulated process which plays an important role in various cardiovascular diseases particularly in myocardial infarction, reperfusion injury, and heart failure. Over the past two decades, investigations of several pathways have broadened our understanding of programmed cell death. Many anti-apoptotic interventions have targeted ischemia-reperfusion, however only a limited number have been considered at the chronic stage of heart failure. Endogenous in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 135 publications
(188 reference statements)
1
24
0
Order By: Relevance
“…However, the pro-domain of executioner caspases is extremely short. They act downstream in the common pathway, amplifying signals from intrinsic or extrinsic pathways, carrying out the biochemical changes in apoptosis (17). Morphological changes of apoptosis appeared several hours previously, followed by the activation of downstream caspase-3, -6 and -7, the cell death would be inevitable (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, the pro-domain of executioner caspases is extremely short. They act downstream in the common pathway, amplifying signals from intrinsic or extrinsic pathways, carrying out the biochemical changes in apoptosis (17). Morphological changes of apoptosis appeared several hours previously, followed by the activation of downstream caspase-3, -6 and -7, the cell death would be inevitable (18).…”
Section: Discussionmentioning
confidence: 99%
“…20, 21, 22 Myocardial ischemia is due to blockage of the blood flow in the myocardium, leading to a significant change in the energy balance including depletion of ATP. A compensatory response emerges in the cardiomyocytes from the inhibition of fatty acid oxidation to an increase in the flux toward anaerobic glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocyte loss after ischemia is mainly due to apoptosis, necrosis (when the cell is unable to support the apoptotic energetic demands), or commitment to autophagy in an attempt to rescue cell function, 21, 23, 30, 31 all three cell-fates having an important role in the heart after I(A)/R-induced dysfunction. Indeed, prevention of the apoptosis induced by ischemia or anoxia minimizes cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…When faced with ischemia, changes at the level of the failing human cardiac myocyte lead to a defect in contractile function. In addition to this, subsequent reperfusion promotes the activation of various injury responses leading to necrosis, apoptosis or autophagy [4][5][6]. Indeed, ischemic heart postconditioning is one strategy to improve clinical outcomes in patients with coronary heart disease and it has been reported that postconditioning procedures can reduce the infarct size [7,8].…”
Section: Introductionmentioning
confidence: 99%